1977
DOI: 10.1159/000207847
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Morphology in Patients on Regular Haemodialysis Treatment

Abstract: Bone marrow smears from 57 patients with chronic renal failure were morphologically analysed. In 55 patients on regular haemodialysis there was a slight ‘shift to the left’ and a significant eosinophilia within the granulopoiesis concurrently with slight megaloblastic changes of the erythroblasts. It is suggested that these abnormalities are caused by the dialysis procedure and not by the uraemia per se

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…They assumed that the eosino-philia may be the result of a reaction between antigen and antibody of the IgE class or a rebound bone marrow response to the adherence of eosinophils to the dialyser membrane, as was previously reported [7], However, an other study of the blood cells adhering to the dialysis membrane did not find any eosinophils on the membrane, even after an 11-hour hemodialysis [9].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…They assumed that the eosino-philia may be the result of a reaction between antigen and antibody of the IgE class or a rebound bone marrow response to the adherence of eosinophils to the dialyser membrane, as was previously reported [7], However, an other study of the blood cells adhering to the dialysis membrane did not find any eosinophils on the membrane, even after an 11-hour hemodialysis [9].…”
Section: Discussionmentioning
confidence: 84%
“…In 1977, Sjogren and Thysell [7], in a study of bone marrow morphology of patients undergoing regular hemo dialysis, found significantly more eosinophils than in bone marrow of normal subjects. They assumed that the eosino-philia may be the result of a reaction between antigen and antibody of the IgE class or a rebound bone marrow response to the adherence of eosinophils to the dialyser membrane, as was previously reported [7], However, an other study of the blood cells adhering to the dialysis membrane did not find any eosinophils on the membrane, even after an 11-hour hemodialysis [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood contains only a small fraction of the total number of eosinophils in the body, and elevated circulating levels of ECP in the absence of peripheral eosinophilia may therefore reflect an increased total eosinophil mass located in other tissues than blood. As a matter of fact, previous studies have demonstrated a strong relationship between uremia and marrow eosino philia, albeit normal blood eosinophil counts [3,17]. The nature of the stimuli resulting in marrow eosinophilia is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…The rebound leuko cytosis that occurs following the acute leukopenia has been shown to be partly due to the release of neutrophils from the bone marrow [3,27]. These newly released neu trophils also show decreased adherence [25], Although there has been no demonstration that these laboratory studies of WBC function have adverse clinical correlates, it is well known that granulocyte adherence, chemotactic and phagocytic activities are essential mech anisms in the complex process for combating infection [28,29].…”
Section: Discussionmentioning
confidence: 99%